Performance of supplemented heifers on Marandu grass pastures in the wet-to-dry transition and dry seasons - Oliveira, Amanda Prates [UNESP]; Bertipaglia, Liandra Maria Abaker; Melo, Gabriel Mauricio Peruca de; Berchielli, Telma Teresinha [UNESP]; Ruggieri, Ana Cláudia [UNESP]; Casagrande, Daniel Rume; Reis, Ricardo Andrade [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of the present study was to evaluate the characteristics of the sward canopy of Marandu grass during the rainy season, the wet-to-dry transition and the dry seasons, between March and September 2004, under intermittent grazing, and to correlate those characteristics with the performance of crossbred heifers receiving mineral supplements ad libitum or protein supplements. The experiment consisted of a randomized block design with three blocks (set of 13 paddocks), each containing five crossbred heifers per experimental unit, totaling 15 replicates. The heifers were given protein supplements daily in individual stalls and received an average 4 g/kg/day of the supplement during the rainy season and 5 g/kg/day during the dry season. Their weight gain was assessed monthly. The pasture structure was assessed through destructive sampling, and the bromatological composition of esophageal extrusa samples was also assessed. Analysis of variance was used to assess performance, and regression analysis was used to evaluate the sward canopy characteristics in relation to the months of the year. A cluster procedure was used to determine the similarity between the months of the year under assessment. Two different groups were formed for pasture evaluation: one group including the months of March to July and another group including the months of August and September. The first group exhibited a better canopy structure than the second group. This fact was corroborated by the animal performance, which was lower during the months of the second group. Low-intake protein supplementation was effective in increasing the performance of the grazing heifers. Pasture structure is critical for animal performance in a grazing environment, regardless of the type of supplementation.
Keywords: nutritional value; pasture management; Supplement; tropical grass; Weight gain